Passivation of Liquid-Phase Crystallized Silicon With PECVD-SiNx and PECVD-SiNx/SiOx - Preissler, Natalie (2018)
Silicon nitride (SiNx) and silicon oxide (SiOx) grown with plasma-enhanced chemical vapor deposition are used to passivate the front-side of liquid-phase crystallized silicon (LPC-Si). The dielectric layer/LPC-Si interface is smooth and layers are well-defined as demonstrated with transmission electron microscopy. Using electron energy loss spectroscopy a thin silicon oxynitride is detected which is related to oxidation of the SiNx prior to the silicon deposition. The interface defect state density (D-it) and the effective fixed charge density (Q(IL,eff)) are obtained from high-frequency capacitance-voltage measurements on developed metal-insulator-semiconductor structures based on SiOx/SiNx/LPC-Si and SiOx/SiNx/SiOx/LPC-Si sequences. Charge transfer across the SiNx/LPC-Si interface is observed which does not occur with the thin SiOx between SiNx and LPC-Si. The SiOx/SiNx/LPC-Si interface is characterized by Q(IL,eff)>10(12)cm(-2) and D-it,D-MG>10(12)eV(-1)cm(-2). With SiOx/SiNx/SiOx stack, both parameters are around one order of magnitude lower. Based on obtained Q(IL,eff) and D-it(E) and capture cross sections for electrons and holes of sigma(n)=10(-14)cms(-1) and sigma(p)=10(-16)cms(-1), respectively, a front-side surface recombination velocity in the range of 10cms(-1) at both interfaces is determined using the extended Shockley-Read-Hall recombination model. Results indicate that field-effect passivation is strong, especially with SiOx/SiNx stack.